The Importance of Lexical Skills in English Language Learning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Developing lexical skills is a critical aspect of language acquisition for English language learners (ELLs), significantly impacting their overall proficiency and confidence. This exploration highlights various strategies and activities that educators can implement to enhance vocabulary acquisition and effective usage. Key approaches include contextual learning, where vocabulary is taught within meaningful contexts, enabling learners to understand and retain words more effectively. Techniques such as word mapping and thematic vocabulary lists help students make connections between words, enhancing their comprehension and application. Interactive activities, including games and role-playing, foster engagement and motivation, while technology integration provides additional resources for practice and reinforcement.